(untitled) (Baghdad Science Journal, 2011)
Study the effect of additives polymer polyvinyl alcohol (PVA) after solving in water by concentration 10% since represent a standard of PVA solution with added to cement – silica composite of ratio (1:2) with 5%, 10%, 15%, 20%, and 25% respectively to the standard quantity of water which using as a mortar of building. The results are demonstrate increasing on compression resistance with increase of PVA solution until 20%, and decreasing of thermal conductivity which represent a composite are increasing in thermal insulating. The results were recommended decreasing of water absorption with increase of PVA solution ratio as illustrated in this study.